Efeitos de barreiras geomorfológicas na estrutura populacional de Astyanax xavante Garutti & Venere, 2009 (Characidae) : bases genéticas e morfológicas para a conservação - Reis, Katiuscia Vilela dos (2012)
Astyanax xavante Garutti & Venere (2009) is a small Characid fish, with its distribution restricted to the Avoadeira stream where it forms groups with up to 150 individuals along the irregular topography of Serra Azul State Park at east Mato Grosso State. This study aimed to characterize the population structure and to evaluate the genetic diversity among four A. xavante stocks micro-isolated by the three highest waterfalls of the stream. This was based on mitochondrial DNA control region and analysis of morphometric ratios. Selected sampling sites included the proximity with headwaters, two intermediary sites and one located downstream. A partial segment of the gene tRNA(Thr), the complete region of the gene to tRNA(Pro) and part of the control region from 50 individuals from each sampling site were sequenced. Genetic-population analyses of nucleotide sequences were carried out using DnaSP and Arlequin software. We found 24 haplotypes, 79% of them were shared by all individuals, 15% were less representative among the stocks and the other 6% constitute rare haplotypes. Nucleotide and haplotype diversity (h = 0,5693 and π = 0,001472) are low when compared with other Characiformes species. The inbreeding coefficient from the Molecular Variance Analysis among stocks (98% of variation encountered within the population) indicates this species as highly homogeneous. Neutrality test result (Fu = -5,36785 p<0,05) indicates the occurrence of population expansion processes characterized by excessive recent mutations. Haplotype net represented a high degree of sharing among haplotypes. We noted a tendency to increasing nucleotide variability among A. xavante stocks, characterizing a unidirectional gene flow from headwaters following stream flow. Morphometric ratios of body height, head height, head length, and pre-dorsal distance are strong variables to predict and explain A. xavante distribution among geomorphological barriers along the stream. Information about gene flow extension and inexpressive morphological variation among stocks of A. xavante is fundamental as a base for management and conservation actions to be taken for this species.